Jewish culture between canon and heresy - Biale, David 1949-2024 (Stanford studies in Jewish history and culture, 2023)
This career-spanning anthology from prominent Jewish historian David Biale brings over a dozen of his key essays together for the first time. These pieces, written between 1974 and 2016, are all representative of a method Biale calls "counter-history": "the discovery of vital forces precisely in what others considered marginal, disreputable and irrational." The themes that have preoccupied Biale throughout the course of his distinguished career-in particular power, sexuality, blood, and secular Jewish thought-span the periods of the Bible, late antiquity, and the Middle Ages to the twentieth century. Exemplary essays in this volume argue for the dialectical relationship between modernity and its precursors in the older tradition, working together to "brush history against the grain" in order to provide a sweeping look at the history of the Jewish people. This volume of work by one of the boldest and most intellectually omnivorous Jewish thinkers of our time will be essential reading for scholars and students of Jewish studies